Review on Plant-Based Management in Combating Antimicrobial Resistance - Mechanistic Perspective - Arip, Masita; Selvaraja, Malarvili; R, Mogana; Tan, Lee Fang; Leong, Mun Yee; Tan, Puay Luan; Yap, Vi Lien; Chinnapan, Sasikala; Tat, Ng Chin; Abdullah, Maha; K, Dharmendra; Jubair, Najwan (Frontiers in Pharmacology, 2022)
Antimicrobial resistance (AMR) is one of the top 10 life-threatening global health problems needed multilevel attention and global cooperation to attain the Sustainable Development Goals (SDGs) according to the World Health Organization (WHO). To identify currently available AMR and pharmacological therapies, the importance of plant and secondary metabolites as a possible solution for AMR with the mechanism of action of the metabolites followed by the role of probiotics, bacteriophages, and biogenic nanoparticles in battling with AMR. All the information were obtained from the government databases, WHO websites, PubMed, Google search, Springer, and Science Direct for articles or any form of publications related to AMR, emphasizing different resistant microbes, current treatments available to treat the resistant microbes, and finally the importance of plants and their secondary metabolites and their discovery as novel agents and their mechanism of action in treating AMR in bacteria, viruses, fungi, and parasites. In most circumstances, AMR is driven by misuse/ overuse of antibiotics which is usually disregarded followed by genetic factors. These conditions escalate resistance against the microbes. Therefore, it is crucial to identify potent and efficient therapeutic agents to treat AMR. Various plants and their associated secondary metabolites are identified and discussed with their mechanism of action for each microbe (bacteria, viruses, fungi, and parasites). Probiotics also identified may help ease the condition and the AMR condition can be altered using bacteriophages and biogenic nanoparticles. AMR is regarded as a significant warning to global healthcare. Plant derivatives such as secondary metabolites along with other alternative choices including probiotics, bacteriophages, and biogenic nanoparticles may be considered as potential therapeutic targets to mitigate the non-ending AMR.